Suplementação de Bovinos na Fase de Recria - Borges, Vinícius Amaral (Universidade Federal do Tocantins, 2022)
Supplementation with protein concentrate and energy concentrate in the rearing phase is an important tool to enhance the results of animals raised on pasture, as the pastures used in the country do not exploit the animals' full genetic potential. For that, a bibliographical research was carried out, under the guidance of Prof. Dr. João Vidal de Negreiros Neto. This work aimed to qualitatively analyze the benefits of supplementation in animals in the rearing phase. The analysis of this study showed a growing need for supplementation of these animals at this specific age, not only by increasing the weight gain of animals, making the productive cycle of animals turn faster, but also the possibility of raising more animals in a smaller pasture area, increasing the stocking rate. And so, to make the animals arrive in slaughter conditions in the shortest period of time, with better carcass characteristics compared to animals grazing without supplementation.